PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN TOKO ONLINE TIME UNIVERSE STUDIO - Maryati Maryati; M. Khoiri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to find out how product quality, service quality and promotion on consumer purchasing decisions at the Time Universe Studio Online Store. The number of respondents in this study was 100 consumers who were taken as research samples. The data collection technique used is a questionnaire. The data that has been collected is then analyzed using multiple statistical analysis methods with SPSS Version 22. Based on the results of the analysis that has been carried out, it shows that there is a partial and simultaneous influence between product quality, service quality and promotion on consumer purchasing decisions at the Universe Studioa Online Store with a value of t count 2.029> t table 1.984 on product quality variable. For the influence of service quality on consumer purchasing decisions at the Time Universe Studio Online Store with a t value of 2.071 > t table of 1.984. While the effect of the Promotion variable on consumer purchasing decisions at the Time Universe Online Store with a t-count value of 2.602 > t-table 1.984. It can be seen from the results of the study that product quality, service quality and promotions each have a partial effect on purchasing decisions for the Time Universe Studio Online Store. While the calculated F value obtained is 5.226 > F table 2.70, which shows that there is a simultaneous influence of the three independent variables on the dependent variable in this study.